Northwest California : a natural history - Sawyer, John O. (John Orvel), 1939-2012 (University of California Press, 2006)
Northwestern California is mainly known for its majestic redwood forests and incomparable coastline, but there is much more in its rich biota and scenery. The forests are part of the most diverse temperate coniferous forest in the world. Rugged mountains, numerous lakes, wilderness areas, and wild rivers attract outdoor enthusiasts and geologists came here to refine the theory of plate tectonics. Distilling a vast amount of knowledge, this book is the starting point for anyone who wants to explore the biological and geographical richness of northwestern California. John O. Sawyer describes the.